2014
DOI: 10.1007/s12471-014-0518-z
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery-bronchial artery fistulas: report of two Dutch cases with a review of the literature

Abstract: BackgroundCoronary bronchial artery fistulas (CBFs) are rare anomalies, which may be isolated or associated with other disorders.Materials and methodsTwo adult patients with CBFs are described and a PubMed search was performed using the keywords “coronary bronchial artery fistulas” in the period from 2008 to 2013.ResultsTwenty-seven reviewed subjects resulting in a total of 31 fistulas were collected. Asymptomatic presentation was reported in 5 subjects (19 %), chest pain (n = 17) was frequently present follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…They proposed that 2 factors regulate the reopening and growth of arterial communications: disequilibrium of the pressure gradient between the 2 arteries and obstruction of the coronary arteries. Additionally, several case series have implied the possibility of a relationship between coronary-bronchial artery fistula and known bronchiectasis [2,5]. Similar to the patients who have previously been described, our patient also suffered from bronchiectasis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…They proposed that 2 factors regulate the reopening and growth of arterial communications: disequilibrium of the pressure gradient between the 2 arteries and obstruction of the coronary arteries. Additionally, several case series have implied the possibility of a relationship between coronary-bronchial artery fistula and known bronchiectasis [2,5]. Similar to the patients who have previously been described, our patient also suffered from bronchiectasis.…”
Section: Discussionsupporting
confidence: 82%
“…According to a review article from the Netherlands, only 31 such fistulas were reported in the period from 2008 to 2013 [2]. Due to the advanced radiologic techniques that are currently used, such as MDCT, diagnosing coronary-bronchial artery fistula has become less complicated [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Said et al suggested the possibility of the reopening of a preexisting non functional congenital communications between the bronchial arteries. they proposed that two factors regulate the reopening and growth of the arterial communication: Desequilibrium of the pressure gradient between the two arteries and obstruction of the coronary artery [8]. Many case series have implied the possibility of a relationship between CBF and bronchiectasis in one or both lungs [9].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic bronchial artery fistula may be silent, or present with chest pain or hemoptysis. 1 It is usually related with bronchiectasis. Various imaging modalities should be considered to identify multiple fistulas, or the course and termination site of the fistula.…”
mentioning
confidence: 99%